Processes of Obtaining Nanostructured Materialswith a Hierarchical Porous Structure on the Example of Alginate Aerogels - Natalia Menshutina; Olga Fedotova; Andrey Abramov; Eldar Golubev; Yan Sulkhanov; Pavel Tsygankov (Gels)
Currently, materials with specific, strictly defined functional properties are becoming increasingly important. A promising strategy for achieving these properties involves developing methods that facilitate the formation of hierarchical porous materials that combine micro-, meso-, and macropores in their structure. Macropores facilitate effective mass transfer of substances to the meso- and micropores, where further adsorption or reaction processes can occur. Aerogels represent a promising class of materials for implementing this approach. The formation of hierarchical porous structures in aerogels can be achieved using soft and hard templating methods or by foaming techniques. This paper presents a comprehensive study of three methods for forming hierarchical porous structures in alginate aerogels: (1) employing surfactants (Pluronic F-68), (2) using zein as a pore-forming component, and (3) foaming in a carbon dioxide medium. The results of micro-CT showed that each of the methods contributes to the formation of macropores within the structure of the resulting aerogels. Size distribution curves of the detected macropores were obtained, showing the presence of macropores ranging from 16 to 323 μm in size for samples obtained using surfactants, from 5 to 195 μm for samples obtained using zein, and from 20 μm to 3 mm for samples obtained by foaming in a carbon dioxide medium. The SEM images demonstrated the macro- and mesoporous fibrous structure of the obtained materials. The nitrogen porosimetry results indicated that samples obtained using surfactants and zein are characterized by a high specific surface area (592–673 m2/g), comparable to the specific surface area for an alginate-based aerogel obtained without the use of pore-forming components. However, the use of the developed methods for the formation of a hierarchical porous structure contributes to an increase in the specific mesopores volume (up to 17.7 cm3/g). The materials obtained by foaming in a carbon dioxide medium are characterized by lower specific surface areas (112–239 m2/g) and specific mesopores volumes (0.6–2.1 cm3/g). Thus, this paper presents a set of methods for forming hierarchical porous structures that can obtain delivery systems for active substances with a controlled release profile and highly efficient platforms for cell culturing.